Lipid-Lowering and Antioxidant Functions of Bottle Gourd () Extract in Human Dyslipidemia - Charu Katare PhD; Sonali Saxena PhD; Supriya Agrawal MSc; Anish Zacharia Joseph PhD; Senthil Kumar Subramani MSc; Dhananjay Yadav PhD; Nita Singh MSc; Prakash Singh Bisen PhD, DSc; G. B. K. S. Prasad PhD (SAGE Publishing, 2014)
The study validated the antidyslipidemic, antioxidant, and antihyperglycemic effects of Lagenaria siceraria fruit extract in human subjects with dyslipidemia along with subjects of normal health. A total of 200 mL of freshly prepared Lagenaria siceraria fruit extract was administered daily on empty stomach for 90 days. Significant reductions ( P < .01) were found in triglycerides and total cholesterol levels in blood. Cardiac risk ratio, atherogenic coefficient, and atherogenicity index of plasma were also improved. Appreciable reductions in body mass index ( P < .01) and blood pressure (systolic P < .01, diastolic P < .05) along with a significant reduction ( P < .05) in fasting blood glucose levels were also observed in these subjects. Lagenaria siceraria fruit extract exhibited significant antioxidant activity in dyslipidemic subjects as evident from elevations in SOD ( P < .05) and GSH levels ( P < .01) with marked improvement in catalase ( P < .01) and TBARS levels ( P < .05). Phytochemical screening confirmed the presence of saponins, glycosides, flavonoids, terpenoids, and phenolic compounds. Lagenaria siceraria fruit extract serves as dietary adjunct in treatment of human dyslipidemia and cardiovascular disease.